PENGARUH PEER GROUP EDUCATION TENTANG SADARI TERHADAP TINGKAT PENGETAHUAN REMAJA PUTRIMENGENAI SADARI (PEMERIKSAAN PAYUDARA SENDIRI)DI SMAN 1 GONDANG KABUPATEN MOJOKERTO - Virda Yuniarti, Enny; Rismawati, Arina (JURNAL KEPERAWATAN SEHAT, 2015)
Breast cancer is general ferocity in which it often happens on women’s population throughout the world and it is one of women death causes. Early detection on breast cancer is truly crucial since its recovery level is high around (80-90%) through breast care activity. By means of peer group education, sensitive messages are able to be delivered openly and easely, so that adolescents have higher knowledge about reproduction health. The purpose of this study at investigating the influence of peer group education about breast care toward adolescent girls’ knowledge level on breast care in SMAN 1 Gondang Mojokerto Regency. This study used pre-experimental research desgin with one group pre test – post test design. The data were collected by using questionnaire applied before and after peer group education. After data collection, the data were processed through some terms including editing, coding, scoring and tabulating with cross tabulation. The findings revealed that there were the influence of peer group education about breast care toward adolescent girls’ knowledge level on breast care in SMAN 1 Gondang Mojokerto Regency. The achievement level of peer group education about breast care toward adolescent girls’ knowledge level on breast care was on before peer group education small proportion of respondents had good knowledge (20,7%) and after peer group education performed almost entirely of respondents had a good knowledge (86,2%). This term happened because respondents were applied group process through discussion.Key words: Breast cancer, Breast care, Peer group education